SISTEM INFORMASI PENJUALAN PADA CV.PUTRA BATANGHARI: CV. Putra Batanghari;MySQL;Sales Information Systems;Visual Basic. Net, 2020. - Yeniwati, Desi; -, Nilawati (LP2M Universitas Nurdin Hamzah, 2021)
Information systems have become an urgent need in various fields of life including in the business field, CV. Putra Batanghari is a company engaged in the sale of stones. Sales information system is needed by CV. Putra Batanghari, because it has a role to facilitate the activities or business activities, especially in sales activities. One information system that can be used is Visual Basic. Net is a simple programming which is expected to make it easier for the CV. Putra Batanghari to prevent errors in inputting sales data and avoid misunderstanding between consumers The design built includes consumer data, item data, transaction data, and report data to produce reports in the form of goods and sales transaction data reports in order to help and process data more effectively and efficiency.